LAJU FILTRASI GLOMERULUS PASIEN DIABETES MELITUS TIPE II DI SALAH SATU RUMAH SAKIT SWASTA DI KABUPATEN DEMAK - Rukminingsih, Fef; Widiastuti, Mei (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Diabetes Mellitus (DM) Type II is a group of metabolic diseases with hyperglycemia characteristics. The use of oral hypoglycemic drugs (OHO) lasts for a relatively long time. Most of the OHO is excreted through the kidneys. This study aims to determine the Glomerulus Filtration Rate (GFR) of type 2 DM patients who use OHO at the